Drop weight impact tests on composite sandwich panel of aluminum foam and epoxy resin. Issue 4 (16th February 2021) - Xin, Yajun; Yan, Huiming; Cheng, Shuliang; Li, Huijian
Abstract: The composite sandwich panel of aluminum foam and epoxy resin uses epoxy resin and aluminum foam interpenetration to form a composite surface layer, which makes the surface layer and core material a whole and greatly improves the integrity of the sandwich panel. In this paper, the failure modes of the sandwich panel is studied by drop weight impact tests and compared with traditional sandwich panel. The effects of impact velocity, composite layer thickness and hammerhead shape on the dynamic impact property of the composite sandwich panel are analyzed. The force–time curves, force–displacement curves and energy–time curves were obtained, and the maximum impact force and impact duration time of each group are compared. The results show that the composite sandwich panel exhibits good stability, integrity and energy absorption capability under the impact load. The hammerhead shape has great effect on failure modes and maximum force, and the impact velocity has great effect on the impact duration time. The maximum impact force is affected by composite layer thickness. However, all the factors have little effect on energy absorption capability but greatly affected the growth rate of energy absorption.